A educação jesuítica nas cartas de Anchieta – ensino da leitura e da escrita no Brasil do século XVI - Santos, Almir Grigorio dos (2018)
This thesis is within the research approach History of Linguistic Ideas, of the Program of Postgraduate Studies within Portuguese Language of the Pontifical Catholic University of São Paulo. It has as analyzes’ object the letters of Anchieta, drafted between 1554 and 1594. The principal goal of this research is to verify within the letters how Anchieta priest saw the education. The objectives are: a) to exhibit the structure of Anchieta's letters and b) to analyse in Anchieta's correspondence the contributions to Brazilian education of the sixteenth century. The formal education in Brazil was initiated by the priests of the Jesus’ company in 1553. Its members were men who lived not only for the teaching, such as it was primary, secondary and superior, but also of indoctrination. They traveled the world propagating the faith, instituting a place of teaching where they arrived and implanting the European’s culture. For the good achievement of the mission, the Jesuits wrote letters addressed to superiors. The paper is based on theorists of the History of Linguistic Ideas, the Annales and the Cultural History, such as Auroux, Burke, Chartier, Fávero & Molina. Through the collection and analysis of the letters written by Anchieta during the period in which he was in the Jesus’ company in Brazil, the correspondence structure and the education thematic are verified. As thesis’ conclusion we affirm that Anchieta, with his ideas, innovated the teaching within Brazil when he was understood that learning the Tupi it would be easier to teach the European’s language to the Indians